The whitewashed tombs - Quartey, Kwei (Quartey, Kwei. Emma Djan mysteries, 2024)
"Marcelo Tetteh, a twenty-seven-year-old LGBTQ activist, is butchered to death one night after being lured on Grindr to a deserted building site. With high instances of homophobia in Ghana, Marcelo's wealthy father doesn't trust the Ghana Police Service to find the killer, so he goes to the Sowah Private Investigators Agency for help, partly because he still feels guilty for disowning his son when he came out. Emma is assigned the case, but quickly learns of a complication that prevents her from teaming up as usual with Jojo, her trusted colleague. Emma is the only one at work who knows Jojo is gay, and now he reveals something else: for some time, Jojo was dating Marcelo, the victim. Working with Manu, whom she's never gotten along with at work, Emma goes undercover in several organizations including International Congress of Families, a powerful organization seeking to criminalize homosexuality in African countries. As Emma infiltrates the ICF, she uncovers a web of deceit and hypocrisy and discovers that the mastermind behind the murders is someone much closer than she ever imagined. Emma must race against time to unmask the killer, protect the vulnerable LGBTQ community, and bring justice to the victims, all while navigating the dangerous waters of politics, power, and personal secrets."--